The control strategies for E. coli O157:H7 in food processing at the physical, chemical and biological levels - Xu, Chenggong; Xin, Zhongxiang; Yu, Ruishen; Li, Jiaxin; Dan, Wenjia; Dai, Jiangkun (Frontiers in Microbiology, 2025)
In recent years, the infectious diseases caused by pathogenic microorganisms have become one of the most prominent public health issues, which seriously endangers people’s lives and leads to significant economic losses. Studies have shown that the Shiga toxin produced by Escherichia coli O157:H7 (E. coli O157:H7) can cause severe diseases, such as hemorrhagic colitis, diarrhea, hemolytic uremic syndrome, etc. For the purpose of improving people’s health level and quality of life, it is quite important and necessary to further deepen the research on the antibacterial methods for pathogenic bacteria. In this work, we mainly summarized the control strategies for E. coli O157:H7 in food processing from the physical, chemical and biological levels, and summarized their own antibacterial mechanisms as well as the advantages and weaknesses. In general, physical methods are effective in eliminating E. coli O157:H7, but some are costly, complex, and may compromise food quality. Chemical methods, such as acidic preservatives and chlorine-based disinfectants, can also pose health risks with long-term and excessive use. In contrast, biological methods, although somewhat expensive, tend to provide safer and more environmentally friendly approaches with effective antimicrobial effects.